Pengaruh Warna di Ruang Kamar Tidur Terhadap Produktivitas Selama Pandemi pada Mahasiswa - Meliana, Meliana; Darmayanti, Tessa Eka (Waca Cipta Ruang, 2023)
The work from home (WFH) activity is one of the methods in the teaching and learning system activities from home that are set at every educational institution by the government. Every student does not take part in teaching and learning activities at the university but remains at home with the aim of preventing the risk of contracting the Covid- 19 coronavirus. Students can spend time a long time in the bedroom compared to other rooms in the house. Factors that can affect productivity, namely the color element in the bedroom space can affect student performance. The role of color for humans has a psychological and psychological effect. The purpose of this study is to examine the effect of color as an important aspect of the interior to be able to choose colors that can have an effect and colors that are not right in increasing work productivity. The selection of the right color contributes to the formation of a comfortable and comfortable room atmosphere and also the teaching-learning performance process for students is better in color. The method used is a qualitative method by conducting interviews with students. The contribution of this study is expected to help the interior in choosing the right color in the room and space with the function of the workspace.